Optimizing Banana Supply Chains In Andhra Pradesh: A Fight For Fairness - Ms. N. Sridevi Parvathi; Dr Ganga Vidya (Revista Electronica de Veterinaria, 2024)
This study delves into the challenges faced by banana producers in East Godavari district, Andhra Pradesh, due to inefficient marketing channels and the dominance of middlemen. By analysing the costs, efficiency, and price spreads across various channels, the research aims to identify strategies for empowering farmers and improving market outcomes.Three primary marketing channels were identified: (1) Farmer-Commission Agent-Wholesaler-Retailer-Consumer, (2) Farmer-Wholesaler-Retailer-Consumer, and (3) Farmer-Retailer-Consumer. Channel selection is influenced by factors such as distance, market availability, and the bargaining power of intermediaries.The study examines the costs associated with each channel, including transportation, storage, and commission fees. Price spreads between farmers and consumers are analyzed to determine the share captured by intermediaries. Additionally, the overall efficiency of the marketing system is assessed based on factors like timeliness, market access, and price stability.Findings reveal significant challenges faced by farmers in achieving fair prices due to the dominance of middlemen. The study recommends strategies to reduce the power of intermediaries, improve market access for farmers, and enhance the overall efficiency of the banana marketing system. By implementing these measures, farmers can increase their income, improve the sustainability of banana production, and contribute to the economic development of the region.